2008
DOI: 10.1007/s00384-008-0507-z
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative irradiation with 5 × 5 Gy in a murine isolated colon loop model does not cause anastomotic weakening after colon resection

Abstract: We developed a new isolated loop model for intermittent irradiation of the colon. Preoperative irradiation of the distal part of a colon anastomosis was successfully administered with acceptable side effects and did not cause reduced tissue oxygenation nor clinical signs of anastomotic weakening, nor objective reduction in bursting pressure and breaking strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The significant reduction in colon mtDNA content in group 2 ( Figure 4A) when compared with patients in group 3 could be attributable to chemotherapy; however, the reason for the reduction of mtDNA content in group 1 remains unclear. Because radiochemotherapy increases ROS production (28)(29)(30)(31), the results of the present study may lend support to the initial hypothesis that, in patients with dehiscence, there should be a greater development of ROS inside the mitochondria.…”
Section: Discussionsupporting
confidence: 76%
“…The significant reduction in colon mtDNA content in group 2 ( Figure 4A) when compared with patients in group 3 could be attributable to chemotherapy; however, the reason for the reduction of mtDNA content in group 1 remains unclear. Because radiochemotherapy increases ROS production (28)(29)(30)(31), the results of the present study may lend support to the initial hypothesis that, in patients with dehiscence, there should be a greater development of ROS inside the mitochondria.…”
Section: Discussionsupporting
confidence: 76%
“…Traction forces were gauged using a tensiometer (FL100, Kern & Sohn, Balingen, Germany) until the muscular layer was disrupted and the mucosal layer was still visible. This was registered as a loss of force by the tensiometer and the maximum value was recorded as the breaking force [50][51][52][53][54][55]. The experimental setup has been described in detail elsewhere [53,54] and is photographically depicted in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…El-Malt et al 31 reported that preoperative CRT had no harmful effect on the mechanical strength of colonic anastomosis. Besides the studies defending that RT has negative effects on anastomosis healing, 5,32,33 there are also studies [34][35][36] reporting that RT does not impair wound healing. Various outcomes have been reported in the studies investigating the effects of 5-FU on wound healing.…”
Section: Discussionmentioning
confidence: 99%